Sustained improvements by behavioural parent training for children with attention‐deficit/hyperactivity disorder: A meta‐analytic review of longer‐term child and parental outcomes - Dominique P. A. Doffer; Tycho J. Dekkers; Rianne Hornstra; Saskia van derOord; Marjolein Luman; Patty Leijten; Pieter J. Hoekstra; Barbara J. van denHoofdakker; Annabeth P. Groenman (Wiley, 2023)
Abstract Background Behavioural parent training is an evidence‐based intervention for children with attention‐deficit/hyperactivity disorder (ADHD), but little is known about the extent to which initial benefits are maintained. Aims This meta‐analytic review investigated longer‐term (i.e., more than 2 months post‐intervention) child and parental outcomes of behavioural parent training for children with ADHD. Materials & Methods We searched for randomized controlled trials and examined ADHD symptoms, behavioural problems, positive parenting, negative parenting, parenting sense of competence, parent‐child relationship quality, and parental mental health as outcomes. We included 27 studies (31 interventions; 217 effect sizes), used multilevel random‐effects meta‐analyses for between‐ and within‐group comparisons (pre‐intervention to follow‐up and post‐intervention to follow‐up), and explored twelve predictors of change. Results Between pre‐intervention and follow‐up (M = 5.3 months), we found significant small‐to‐moderate between‐group effects of the intervention on ADHD symptoms, behavioural problems, positive parenting, parenting sense of competence and parent‐child relationship quality. Within‐group findings show sustained improvements in the intervention conditions for all outcome domains. There were few significant changes from post‐intervention to follow‐up. Additionally, the large majority of the individual effect sizes indicated sustained outcomes from post‐intervention to follow‐up. There were seven significant predictors of change in child outcomes, including stronger reductions in ADHD symptoms of girls and behaviour problems of younger children. In contrast with some meta‐analyses on short‐term effects, we found no differences between masked and unmasked outcomes on ADHD symptoms at follow‐up. Discussion & Conclusion We conclude that behavioural parent training has longer‐term benefits for children's ADHD symptoms and behavioural problems, and for positive parenting behaviours, parenting sense of competence and quality of the parent‐child relationship.